2020
DOI: 10.1080/09583157.2020.1722798
|View full text |Cite
|
Sign up to set email alerts
|

The potential of highly nutritious frozen stages of Tyrophagus putrescentiae as a supplemental food source for the predatory mite Amblyseius swirskii

Abstract: Astigmatid mites have potential as supplementary prey items to support generalist predator populations in crops. However, applying living prey mites has some disadvantages; if not predated they have the potential to cause crop damage and allergies. In this study, we evaluated various diets based on the astigmatid mite Tyrophagous putrescentiae (Schrank) as a supplemental food source for the predatory mite Amblyseius swirskii Ahias-Henriot. Eggs and larvae of T. putrescentiae were reared on a diet of dog food (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(62 reference statements)
1
18
0
2
Order By: Relevance
“…The following feeding mites could be used to improve the reproduction and survival of predatory mites: Tyrophagus putrescentiae (Schrank) (Pirayeshfar et al, 2020), Carpoglyphus lactis (L.) (Nguyen et al, 2013), Thyreophagus entomophagus (Laboulbene), Suidasia medanensis (Oudemans) (Sánchez et al, 2019), and Aleuroglyphus ovatus (Troupeau) (Xia et al, 2012;Ferrero et al, 2016;Rueda-Ramírez et al, 2018). However, very few trials have been performed at plant level (Hoogerbrugge et al, 2008;Vila et al, 2017;Pirayeshfar et al, 2020) and studies on the actual effect of these strategies on pest control are limited. Pirayeshfar et al (2020) succeeded in increasing Amblyseius swirskii Athias-Henriot numbers on chrysanthemum plants by providing living T. putrescentiae per plant, but failed to do so using frozen T. putrescentiae.…”
Section: Anthocoridsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following feeding mites could be used to improve the reproduction and survival of predatory mites: Tyrophagus putrescentiae (Schrank) (Pirayeshfar et al, 2020), Carpoglyphus lactis (L.) (Nguyen et al, 2013), Thyreophagus entomophagus (Laboulbene), Suidasia medanensis (Oudemans) (Sánchez et al, 2019), and Aleuroglyphus ovatus (Troupeau) (Xia et al, 2012;Ferrero et al, 2016;Rueda-Ramírez et al, 2018). However, very few trials have been performed at plant level (Hoogerbrugge et al, 2008;Vila et al, 2017;Pirayeshfar et al, 2020) and studies on the actual effect of these strategies on pest control are limited. Pirayeshfar et al (2020) succeeded in increasing Amblyseius swirskii Athias-Henriot numbers on chrysanthemum plants by providing living T. putrescentiae per plant, but failed to do so using frozen T. putrescentiae.…”
Section: Anthocoridsmentioning
confidence: 99%
“…However, very few trials have been performed at plant level (Hoogerbrugge et al, 2008;Vila et al, 2017;Pirayeshfar et al, 2020) and studies on the actual effect of these strategies on pest control are limited. Pirayeshfar et al (2020) succeeded in increasing Amblyseius swirskii Athias-Henriot numbers on chrysanthemum plants by providing living T. putrescentiae per plant, but failed to do so using frozen T. putrescentiae. Pirayeshfar et al (2020) suggested that the different diets used to rear the prey mites may have an influence on the population increase of the predatory mites.…”
Section: Anthocoridsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a predator's performance is generally affected by the nutritional quality of prey, which, in turn, is primarily influenced by the prey's diet. For example, the larval stages of the prey mite, T. putrescentiae, reared on a protein-rich and fat-rich diet (dog food), resulted in a high oviposition rate of A. swirskii (Pirayeshfar et al 2020). However, since T. putrescentiae could feed on soft plant tissues and damage crops (Oliveira et al 2007), it is unsuitable as alternative prey when inoculating the predatory mite in greenhouses or agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…Wat hiervoor de reden kan zijn is nog onbekend. Uit onderzoek vanPirayeshfara et al (2020) blijkt dat Californische trips zich niet kan ontwikkelen op T. putrescentiae prooimijten. Of Californische trips zich wel kan ontwikkelen op T. entomophagus prooimijten is nog niet eerder onderzocht.…”
unclassified